2018
DOI: 10.1016/j.rpor.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Interfractional diaphragm changes during breath-holding in stereotactic body radiotherapy for liver cancer

Abstract: Residual intrafractional variability of diaphragm position is minimal, but large interfractional diaphragm changes were observed. There was a small effect in the patient condition difference between pCT and CBCT. The impact of the difference in daily breath-holds on the interfractional diaphragm position was large or the difference in daily breath-holding heavily influenced the interfractional diaphragm change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Although there are many reports on the setup method in SBRT for liver cancer, [11][12][13] there are few reports in PT. It is often observed that the diaphragm location changes from the time of the 1st-CT during the course of PSPT for HCC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are many reports on the setup method in SBRT for liver cancer, [11][12][13] there are few reports in PT. It is often observed that the diaphragm location changes from the time of the 1st-CT during the course of PSPT for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In modern radiation therapy techniques such as SBRT or PT for HCC, the vertebral body, diaphragm, and marker (metal marker or lipiodol accumulation) are generally used as indicators of setup depending on the tumor location. [10][11][12][13] The diaphragm, a typical surrogate for liver motion, is often tracked given its visibility on x-ray images. The setup performed in our institution performs vertebral body matching (VM) in orthogonal x-ray imaging, and then performs matching using the diaphragm or marker as an index.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, position reproducibility is important for accurate position matching in breath-hold irradiation. Previous studies have shown good positional reproducibility results for breath-hold irradiation in end exhalation [ 12 , 14 , 15 ]. Although various methods have evaluated the positional reproducibility of breath-hold irradiation, most of them require manual operation.…”
Section: Introductionmentioning
confidence: 99%